The genome and transcriptome of common milkweed (Asclepias syriaca): resources for evolutionary, ecological, and molecular studies in milkweeds and Apocynaceae - Weitemier,Kevin; Straub,Shannon CK; Fishbein,Mark; Bailey,C Donovan; Cronn,Richard C; Liston,Aaron (PeerJ Preprints, 2018)
Milkweeds (Asclepias) are used in wide-ranging studies including floral development, pollination biology, plant-insect interactions and co-evolution, secondary metabolite chemistry, and rapid diversification. We present the first nuclear genome and transcriptome assemblies of the common milkweed, Asclepias syriaca. This is the first species in Apocynaceae subfamily Asclepiadoideae with reconstructions of the nuclear, chloroplast, and mitochondrial genomes, and the first in the Apocynaceae to have linkage group information incorporated into the nuclear assembly. The genome was sequenced to 80.4× depth and the draft assembly contains 54,266 scaffolds ≥1 kbp, with N50 = 3415 bp, representing 37% (156.6 Mbp) of the estimated 420 Mbp genome. A total of 14,474 protein-coding genes were identified based on transcript evidence, closely related proteins, and ab initio models, and 95% of genes were annotated. A large proportion of gene space is represented in the assembly, with 96.7% of Asclepias transcripts, 88.4% of transcripts from the related genus Calotropis, and 90.6% of proteins from Coffea mapping to the assembly. The progesterone 5β-reductase gene family, a key component of cardenolide production, is likely reduced in Asclepias relative to other Apocynaceae. Scaffolds covering 75 Mbp of the Asclepias assembly formed eleven linkage groups. Comparisons of these groups with pseudochromosomes in Coffea found that six chromosomes show consistent stability in gene content, while one may have a long history of fragmentation and rearrangement. The genome and transcriptome of common milkweed provide a rich resource for future studies of the ecology and evolution of a charismatic plant family.
Keywords: Asclepias; milkweed; Apocynaceae; cardenolide; chromosome evolution; genome; Gentianales; linkage mapping